Vulnerability parameters in picture fuzzy soft graphs and their applications to locate a diagnosis center in cities - R. V Jaikumar; Raman Sundareswaran; Marayanagaraj Shanmugapriya; Said Broumi; Talal Ali Al-Hawary (Journal of Fuzzy Extension and Applications)
The notion of Fuzzy Graphs (FGs) and Intuitionistic Fuzzy Graphs (IFGs) is generalized in the Picture Fuzzy Graph (PFG), which is a more common platform for expressing the degree of positive, negative, and neutral membership functions. Picture Fuzzy Soft Graphs (PFSGs) are powerful mathematical tools for modeling real-world vagueness. The concept of vulnerability parameters of PFSG is provided in this research work by introducing the novel cardinality, domination number, integrity, and Domination Integrity (ÐÏ) of PFSG. Furthermore, a decision-making method for the PFSG has been presented using ÐÏ to suggest an algorithm for determining the ideal location for establishing a city diagnosis center